“ORGANIZADORES GRÁFICOS EN EL APRENDIZAJE DE PRODUCTOS NOTABLES EN LA UNIDAD EDUCATIVA “ISABEL DE GODIN” EN LOS ESTUDIANTES DE DÉCIMO AÑO EN EL PERÍODO SEPTIEMBRE 2019- FEBRERO 2020” - Padilla Toapanta, Mónica Alexandra (2020)
The objective of this research is to determine the relationship that may exist between the use of graphic organizers as a teaching strategy. For this, an investigation has been proposed with a quantitative approach, descriptive, correlational and with a pre-experimental level. The research population came from the tenth year students of Basic and General Education in Isabel de Godin Educational Unit, from September 2019 to February 2020. The students of the tenth “A”, class were selected as a sample. Then, an intentional non-probabilistic sampling technique was employed. The hypothesis proposed was: the average of the post-test is greater than the average of the pre-test. The same was verified through the use of the t-student statistic. It concluded that the application of graphic organizers influences the learning notably. It could be demonstrated trough the comparison of mean, in the students of the tenth, year, class “A”. Therefore, this research recommends the use of graphic organizers within the educational context, as a didactic strategy for developing meaningful learning.